Diethylaminoethyl- chitosan as an efficient carrier for siRNA delivery: Improving the condensation process and the nanoparticles properties - de Souza, Ricchard Hallan Felix Viegas [UNESP] (2018)
Chitosan has been indicated as a promising carrier for the preparation of small interfering RNA (siRNA) delivery systems due to its remarkable properties. However, its weak interactions with siRNA molecules makes the condensation of siRNA molecules into nanoparticles difficult. In this work, a non-viral gene delivery system based on diethylaminoethyl chitosan (DEAE-CH) derivatives of varied Mw (25–230 kDa) having a low degree of substitution of 15% was investigated. The presence of secondary and tertiary amino groups strengthened the interaction of siRNA and DEAE-CH derivatives of higher Mw (130 kDa to 230 kDa) and provided the preparation of spherical nanoparticles at low charge ratios (N/P 2 to 3) with low polydispersities (0.15 to 0.2) in physiological ionic strength. Nanoparticles prepared with all derivatives exhibited remarkable silencing efficiencies (80% to 90%) on different cell lines (HeLa, MG-63, OV-3) by adjusting the charge ratios. A selected PEG-folic acid labeled derivative (FA-PEG-DEAE15-CH230) was synthesized and its nanoparticles completely inhibited the mRNA expression level of TNF-α in RAW 264.7 macrophages. The study demonstrates that the insertion of DEAE groups provides improved physical properties to chitosan-siRNA nanoparticles and holds potential for in vivo applications.